Employment Structures in China from 1990 to 2015: Demographic and Technological Change - Peng Ge; Wenkai Sun; Zhong Zhao (Institute of Labor Economics (IZA), 2021)
Using national representative samples from population census and mini-census of China, this paper documents important employment dynamics in China from 1990 to 2015. The share of routine manual jobs decreased significant from 57% to 32%; both the share of routine cognitive jobs and the share of not-working increased significantly, from 8% to 19%, and from 16% to 31%, respectively; however, the share of non-routine jobs had no significant change. Our decomposition exercises suggest that the composition effect resulting from change in the composition of population demographics, the propensity effect from change in the probability for people with given demographic characteristics into different employment categories and the interaction effect contribute to 68%, 66% and -34% to the fall in routine manual jobs, respectively. Meanwhile, these effects for the rise in routine cognitive jobs and for the increase in not-working are 16%, 74%, 11%, and 7%, 93%, 0.3%, respectively.
Keywords: J21; 330; employment dynamics; routine job; non-routine job; China